Bacillus subtilis CCT-7840 pode ser utilizado como bioinsumo para disponibilizar nutrientes e promover o crescimento do sorgo? - Lauriuchi, Geissielen Andrade (2024)
Conventional agriculture, which employs practices such as soil preparation, pesticides, and genetically modified crops, has significant impacts on the agroecosystem, reducing natural resources and affecting food security amid climate change. In light of this, this research focuses on considering unconventional approaches, such as the use of biological products containing the Bacillus subtilis (B. subtilis) species, with the aim of enhancing nutrient availability in the soil, promoting Plant Growth Promotion (PGP), and assessing the potential of a product with the B. subtilis CCT-7840 strain as a bioinput in conventional sorghum cultivation systems. Parameters such as plant dry mass, soil fertility, grain productivity, soil basal respiration rate, carbon content in microbial biomass, and soil enzymatic potential were examined. The experiment was conducted in the field, following a Randomized Complete Block Design (RCBD), in two distinct soil classes with medium and clay textures, and treatments included inoculum (or lack thereof) distributed across six blocks. All results underwent Analysis of Variance (ANOVA) and the Scott-Knott test, with a significance level of 5%, and a 2x2 factorial analysis scheme (medium and clay-textured soil, with and without inoculum). For non-parametric variables, the Kruskal-Wallis test was employed, with a significance level of 5%. The results indicate that the application of the bacterium did not show significant outcomes as a bioinput in sorghum cultivation. There was no significant increase in above-ground dry mass, soil fertility, sorghum productivity, Soil Basal Respiration (SBR), qCO2, Microbial Biomass Carbon (MBC-S), and enzymatic activity with the use of the product containing B. subtilis